2015
DOI: 10.1377/hlthaff.2015.0685
|View full text |Cite
|
Sign up to set email alerts
|

The Early Impact Of The ‘Alternative Quality Contract’ On Mental Health Service Use And Spending In Massachusetts

Abstract: Accountable care using global payment with performance bonuses has shown promise in controlling spending growth and improving care. This study examined how an early model, the Alternative Quality Contract (AQC) established in 2009 by Blue Cross Blue Shield of Massachusetts (BCBSMA), has affected care for mental illness. We compared spending and use for enrollees in AQC organizations that did and did not accept financial risk for mental health with enrollees not participating in the contract. Compared with BCBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…These findings contribute to evidence of unchanged or improved quality associated with participation in the Medicare ACO programs(57) in general. Our findings are also consistent with recent quantitative research that found limited gains in performance on other behavioral health quality metrics associated with ACOs(11, 13). More generally, the absence of large effects on antidepressant use and adherence in ACOs is consistent with previous documentation that depression is commonly under-recognized and under-treated(14).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings contribute to evidence of unchanged or improved quality associated with participation in the Medicare ACO programs(57) in general. Our findings are also consistent with recent quantitative research that found limited gains in performance on other behavioral health quality metrics associated with ACOs(11, 13). More generally, the absence of large effects on antidepressant use and adherence in ACOs is consistent with previous documentation that depression is commonly under-recognized and under-treated(14).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, leaders of Medicare and commercial ACOs have described considerable challenges in improving behavioral health care management, including inadequate data availability for managing behavioral health due to federal and state privacy restrictions that limit information sharing between behavioral health and general medical providers, incomplete SUD data provided by CMS due to restrictions from 42 CFR Part 2, and shortages of mental health care providers(13, 15). …”
Section: Discussionmentioning
confidence: 99%
“…While AQC provider organizations reported little initial focus on improving integration of behavioral health and other services, many have since initiated efforts to improve such integration (7). It will be critical to understand how these new efforts affect children with ADHD over the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Global payment models, such as the AQC, provide an opportunity to address fragmentation of care by incorporating mental and substance use disorder (behavioral health) services with general medical services under one integrated payment system (6,7). Under this type of model, primary care physicians (PCPs) play the central role in patients' care and are typically given greater flexibility to coordinate the health of the population in their patient panels with attention to reducing the burden of disease over a longer time horizon than is typical in traditional payment models.…”
mentioning
confidence: 99%
“…It is also consistent with knowledge about the implementation of the AQC program itself; AQC organization leaders reported little focus on this area during the AQC’s first three years as they struggled to reorient their systems in response to the AQC. Likewise, leaders of specialty behavioral health provider organizations in Massachusetts have indicated a low level of awareness of the AQC, and no substantial changes in referral patterns or contracting practices due to the AQC (33). …”
Section: Discussionmentioning
confidence: 99%